Pattern of sexually transmitted infections in a tertiary care hospital: A five-year retrospective study - Karki, Anupama; Shrestha, Rushma; Parajuli, Niraj (Grande Medical Journal, 2019)
Introduction: Sexually transmitted infections (STIs) have a profound impact on sexual and reproductive health worldwide and especially in a developing country like Nepal. However, adequate studies are lacking in our context with regards to the pattern analysis of the STIs in community and in the tertiary care hospitals. The aim of this study is to understand the prevalence and pattern of different STIs in Nepal. Methods: This is a retrospective observational study in which the record of all patients who attended the STD OPD of NAMS, Bir Hospital from 2071 to 2075 B.S. (April 2014 – March 2019) have been analyzed. Results: Among the 2658 patients who visited the STD OPD, majority (27.5%) had been diagnosed with syphilis. The second commonest diagnosis was condyloma acuminata accounting for 22.6 % of cases. Urethral discharge syndrome and vaginal discharge syndrome comprised of 20.1% and 17% respectively. Genital herpes constituted 6% of cases whereas genital molluscum contagiosum comprised of 3.4% of cases. Genital ulcer diseases accounted for 2.1% of total cases. Conclusions: There was a high magnitude of STIs found in this study, among which syphilis constituted the major burden. The results of this study also urge further awareness programs regarding the clinical features and importance of early treatment of STIs.